2016
DOI: 10.1080/02670844.2016.1161948
|View full text |Cite
|
Sign up to set email alerts
|

Properties of CdS films doped with magnesium and fluorine

Abstract: Nanostructured CdS thin films co-doped with Mg and F were prepared on glass substrates maintained at 400°C by spray technique using perfume atomiser. Structural, morphological, optical and electrical properties of the films were investigated in order to study the effect of Mg, F doping concentration. XRD patterns confirm that both undoped and co-doped CdS films exhibit hexagonal crystal structure with preferential orientation along the (0 0 2) plane. Crystallite size decreased from 33.19 to 24.51 nm with incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(11 citation statements)
references
References 25 publications
(31 reference statements)
4
7
0
Order By: Relevance
“…Table 2 illustrates the values of direct optical energy gap and the optical constants [refractive index (n), extinction coefficient (k), the real part ( r) and the imaginary part ( i) of dielectric constant ]. Our results are similar to that obtained by Ashour [13] , Moss [15] and Sivaraman [16]. The photoconductivity of the as deposited and annealed films has been determined.…”
Section: Resultssupporting
confidence: 91%
“…Table 2 illustrates the values of direct optical energy gap and the optical constants [refractive index (n), extinction coefficient (k), the real part ( r) and the imaginary part ( i) of dielectric constant ]. Our results are similar to that obtained by Ashour [13] , Moss [15] and Sivaraman [16]. The photoconductivity of the as deposited and annealed films has been determined.…”
Section: Resultssupporting
confidence: 91%
“…It is noticed that the number of bands increased with the increased Cu:S ratio. 38 In case of samples with different Cu:S amount ratio, the band-toband transitions are blue shifted similar to the energy gap behavior obtained from UV-analysis, and this shift is due to the crystallite size effect as discussed in XRD part, In our case as Cu:S ratio increased, the crystallite size decreased, thus the defects increased and number of bands increased (see XRD part).…”
Section: Optical Propertiessupporting
confidence: 82%
“…36 The violet peak can be attributed to near band edge electronic transition (band-to-band transition). 38 In case of samples with different Cu:S amount ratio, the band-toband transitions are blue shifted similar to the energy gap behavior obtained from UV-analysis, and this shift is due to the crystallite size effect as discussed in XRD part, amount of defects created inside the band gap. The blue color peak belongs to transitions of trapped electrons from defects levels (probably S-vacancy states) to the valence band.…”
Section: Optical Propertiessupporting
confidence: 71%
“…It is observed that all the films exhibit emission peaks at 485 nm (2.56 eV), 544 nm (2.28 eV) and 608 nm (2.04 eV). The peak at 485 nm can be attributed to the transitions of trapped electrons from donor levels to the valence band which can be assigned to defect states, probably S vacancy states [24]. The green band emission observed at 2.28 eV has been originated from the transition of the increased V s donors to recombine with S interstitials (I s ) acceptors in the valence band [25].…”
Section: Pl Studiesmentioning
confidence: 99%